2020
DOI: 10.1038/s41598-019-56885-y
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effect on Porosity and Permeability of Shales

Abstract: Porosity and permeability are the key factors in assessing the hydrocarbon productivity of unconventional (shale) reservoirs, which are complex in nature due to their heterogeneous mineralogy and poorly connected nano-and micro-pore systems. Experimental efforts to measure these petrophysical properties posse many limitations, because they often take weeks to complete and are difficult to reproduce. Alternatively, numerical simulations can be conducted in digital rock 3D models reconstructed from image dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…FFT-based methods are particularly effective for analyzing digital volume images of rocks [275][276][277], sedimentary rocks [278] and shales [279]. In this context, the mechanical compression of the digital images is indispensable for simulating the ambient conditions several kilometers below earth's surface [280].…”
Section: Porous and Granular Materialsmentioning
confidence: 99%
“…FFT-based methods are particularly effective for analyzing digital volume images of rocks [275][276][277], sedimentary rocks [278] and shales [279]. In this context, the mechanical compression of the digital images is indispensable for simulating the ambient conditions several kilometers below earth's surface [280].…”
Section: Porous and Granular Materialsmentioning
confidence: 99%
“…Permeability. Porosity and permeability are critical reservoir parameters and reflect depositional and diagenetic processes [46,47]. The measured core porosity of 38 samples ranges from 0.012 to 0.07, averaging 0.04 fraction.…”
Section: Lithofacies and Porosity Andmentioning
confidence: 99%
“…Taking oil shale as an example, characterization and modeling of the pores' shape and connectivity provide essential information on the permeability and gas accumulation space [ 81 83 ]. Unlike the conventional reservoirs of sandstones and carbonates, previous studies have demonstrated that the shale reservoirs are usually dominated by a large number of nanometer pores [ 84 86 ]. Hence, FIB-SEM tomography can robustly identify and characterize the microstructural properties of shale kerogen.…”
Section: Applications Of the Fib-sem Systemmentioning
confidence: 99%